Avaliação da acurácia dos marcadores sorológicos para diagnóstico de doença celíaca - Magda Bahia (2006)
Celiac disease (CD) is the permanent intolerance to gluten, a proteic fraction found in wheat, barley, rye, and oats, and can be controlled with a gluten-free diet. It is triggered by a self-immune mechanism in individuals with genetic predisposition and is related to the presence of HLA-DQ, codified by genes DQA1 and DQB of chromosome six. The aims of the present study were: to determine the efficacy of serological markers - antibodies class IgG and IgA antigliadin (AGAA, AGAG), antibodies class IgA antitransglutaminase (ATGT), antibodiesclass IgA antiendomysial using as substrate human umbilical cord (AAECO) and monkey esophagus (AAEEM) - in the diagnosis of celiac disease through sensitivity, specificity; to establish a relation between them through the analysis of the main components; to compare the efficacy of determining antiendomysial antibodies through indirect immunofluorescence using as substrate monkey esophagus and umbilical cord; and to determine the most adequate sequence ofexams for screening patients for jejunal biopsy in the diagnosis of celiac disease. We studies 400 serum samples from: patients with celiac disease (n=38), patients without gastrointestinal symptoms (n=208) and patients with gastrointestinal symptoms, (n=155). Antigliadin antibodies and antitransglutaminase tecidual antibodies were determined by ELISA and antibodies class IgA antiendomysial were analyzed by indirect immunofluorescence microscopy. Sensitivity and specivity were 81,1% and 95,2 % for AGAA, 89,2% and 95,2%, for AGAG, 83,9% and 96,8% for ATGT, 87,9% and 100,0% for AAECO and 88,6% and 100,0% for AAEEM, respectily. Through statistical analysis of the main components, we cansimultaneously assess several variables and their correlation. In the present study, celiac disease and serological markers present a good correlation, with 94% of inertia. Multivariate analysis showed strong association between AAECO and celiac disease a far the best correlate with the enteropathy, followed by TGT, AGAA, and AGAG. Due association of celiac disease with IgA deficiency, similarity between sensitivity and specificity of AGAA and TGT and their correlations in the multivariate analysis, AGAA and AGAG can be used for the screening, followed byAAECO, provided that a cut-off point for the results of these exams areestablished in developing countries. Results of determining antiendomysial antibodies on the umbilical cord overlapped with those on monkey esophagus. Therefore, umbilical cord should be used as substrate in order to avoid using material from species under risk of extinction.